(untitled) (Notes in Current Biology, 2018)
The article presents the results of analysis of distribution of the dendroflora species composition of the Rivne region artificial protected parks by systematic situation and life forms. There are 25 artificial protected parks in the studied region. 14 of them are located in the Polissya region, and 11 in the broadleaf forests zone. There are 481 species of tree plants (9,52 % Pinophyta, 90,48 % Magnoliophyta) on the territory of investigated objects. As in general, in all parks, and separately, in the objects located within the two parts of the region (Ukrainian Polissya and broadleaf zone), the largest number of genera and species represent the family Rosaceae. As a result of classification of species by biomorph types, three types of species have been identified: trees, shrubs and wood vines. The prevalence of the Magnoliophyta trees is typical for the dendroflora of artificial protected parks of the Rivne region. The difference in the biomorphological structure of the parks located in both parts of the area is observed in the distribution of species by classes of height. There are more trees of the fourth height and high shrubs in the dendroflora of Polissya study objects. The majority of species of trees belong to the first class of height with shrubs being mostly of average height in artificial protected parks in the other part of the region. In general, species of mezophanerophytes life form prevail in the dendroflore of all objects of study (44,30 % in northern objects and 59,63 % in southern objects of research).